AQUATIC BEETLES OF MANIPUR - SHANTIBALADEVI, S.; SINGH, T.K.; SHARMILA, M.; DEVIKARANI, KH. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2011)
Taxonomic studies undertaken on aquatic beetles of Manipur reveals the occurrence of 36 species belonging to the families Dytiscidae, Gyrinidae and Hydrophilidae. Out of these, 17 species are reported for the first time from Manipur. Two species belonging to the two genera namely Hydrovatus and Orectochilus are determined up to generic level.